Tick-borne disease risk in a forest food web - Ostfeld, Richard S.; Levi, Taal; Keesing, Felicia; Oggenfuss, Kelly; Canham, Charles D. (Ecology (Durham), 2018)
Changes to the community ecology of hosts for zoonotic pathogens, particularly rodents, are likely to influence the emergence and prevalence of zoonotic diseases worldwide. However, the complex interactions between abiotic factors, pathogens, vectors, hosts, and both food resources and predators of hosts are difficult to disentangle. Here we (1) use 19 yr of data from six large field plots in southeastern New York to compare the effects of hypothesized drivers of interannual variation in Lyme disease risk, including the abundance of acorns, rodents, and deer, as well as a series of climate variables; and (2) employ landscape epidemiology to explore how variation in predator community structure and forest cover influences spatial variation in the infection prevalence of ticks for the Lyme disease bacterium, Borrelia burgdorferi, and two other important tick-borne pathogens, Anaplasma phagocytophilum and Babesia microti. Acorn-driven increases in the abundance of mice were correlated with a lagged increase in the abundance of questing nymph-stage Ixodes scapularis ticks infected with Lyme disease bacteria. Abundance of white-tailed deer 2 yr prior also correlated with increased density of infected nymphal ticks, although the effect was weak. Density of rodents in the current year was a strong negative predictor of nymph density, apparently because high current abundance of these hosts can remove nymphs from the host-seeking population. Warm, dry spring or winter weather was associated with reduced density of infected nymphs. At the landscape scale, the presence of functionally diverse predator communities or of bobcats, the only obligate carnivore, was associated with reduced infection prevalence of I. scapularis nymphs with all three zoonotic pathogens. In the case of Lyme disease, infection prevalence increased where coyotes were present but smaller predators were displaced or otherwise absent. For all pathogens, infection prevalence was lowest when forest cover within a 1 km radius was high. Taken together, our results suggest that a food web perspective including bottom-up and top-down forcing is needed to understand drivers of tick-borne disease risk, a result that may also apply to other rodent-borne zoonoses. Prevention of exposure based on ecological indicators of heightened risk should help protect public health.